KAJIAN ASPEK ERGONOMI MIKRO PADA SISTEM KERJA AGRO INDUSTRI (Studi Kasus Pabrik Gula Pada Proses Tebang Angkut Dan Giling) - Lamto Widodo; Bambang Pramudya; Sam Herodian; M. Faiz Syu’aib (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Agro-industrial work system, especially the sugar industry is a very complex work systems. In the approach to ergonomics, system components can be divided into human (workers), equipment and materials, physical environment and organizational environment. Each component interacts with the pattern of interrelation in the principle of autopoeisis (self-organizing system). Ergonomics analysis of the each component are needed in order to design or redesign the system, to ensure that work system can be sustainabe. This paper discusses some of the ergonomic aspects of work systems, among others, physical workload of manual harvesting, manual transporting of sugarcane and physical environmental conditions in the factory include vibration, temperature, noise, and lighting, as well as employee perceptions of work facing the system. Based on the comparison value IRHR (increase ratio of heart rate) for each job, the workload of manual harvesting categorized in moderate and severe categories (IRHR between 1.27 to 1.66) and manual transporting categorized in heavy and very heavy (IRHR between 1.43 to 1, 93). The physical condition of the factory there are some of the data beyond the allowed limit, for example, the highest temperature reached 37 0C, very low illumination of 7.5 lux, and the noise reached 93.2 dB. While the boiler operator workload is very heavy category (IRHR 1.67). From some of these results, it can be concluded that conditions are less ergonomic work systems, and requires some improvement in microergonomics aspects.